Metodologi Living Hadis, Pengertian, Tujuan dan Implementasinya - R, Rismah; Amin, Muhammadiyah; Yahya, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Living hadith can be interpreted as a reality that applies in Islamic society and is believed to originate from hadith that has taken root and is attached and then developed in the midst of society and it is considered true because it comes from the Hadith of the Prophet SAW. and is practiced consistently by society. In the scope of hadith interpretation, the study of the science of the Qur'an and Hadith generally takes four forms, namely: the first three forms lead to cultural phenomena, namely: text studies (text interpretation), studies of re-reading of texts (text reinterpretation), text reconstruction. The fourth is the study of Muslim social phenomena related to the text of the Qur'an and the hadith of the Prophet SAW. The Living Hadith methodology aims to identify the manifestation of hadith in social traditions, bridge the gap between hadith texts and contemporary reality, and analyze society's response to hadith. In addition, this methodology seeks to uncover hadith-based behavioral patterns in modern life and support the formation of a religious society through the practical implementation of hadith values. With this approach, Living Hadith is expected to be able to strengthen the relevance of hadith in the lives of modern society.